A STUDI KOMPARATIF HAK WARIS ANAK LUAR NIKAH PERSPEKTIF HUKUM ISLAM DAN HUKUM PERDATA: STUDI KOMPARATIF HAK WARIS ANAK LUAR NIKAH PERSPEKTIF HUKUM ISLAM DAN HUKUM PERDATA - Fathor, Rozy; Izzuddin, Ahmad (CV. Kalimasada Group, 2024)
This research is driven by the fact that in Islamic inheritance law and civil law there are quite a lot of differences. This study aims to find out how the law of inheritance of legal children out of wedlock between Islamic inheritance law and civil law. This research uses a qualitative approach with library research data collection techniques, namely using books, journals, papers, theses, articles, and literature related to related problems that aim to underlie the theoretical basis of writing this journal. The results of the conclusions in this study, it was found that the first factor in terms of the rate of distribution of heirs from extramarital children; Then the second factor is to discuss inheritance rights if the child out of wedlock dies; And the third factor in Article 873 of the Law, an out-of-wedlock child is entitled to inherit the entire inheritance if one of the blood relatives dies. Keywords : Islamic law, inheritance rights, civil law